Telehealth to Improve Physical Activity in Adults with Diabetes Mellitus: A Narrative Review - Triana Karnadipa; Ari Nurfikri; Safrin Arifin (Universitas Aisyah Pringsewu, 2022)
Physical activity has been evaluated to decrease mortality rates in people with diabetes mellitus. After the COVID-19 pandemic, healthcare delivery was leaned towards telemedicine or telehealth to conduct social distancing. The primary aim of this review is to evaluate formats and strategies used in telemedicine to improve physical activity in adults with diabetes mellitus. ProQuest, Medline, and CINAHL were searched for studies involving adults with diabetes mellitus (more than 18 years old); telemedicine; and physical activity outcomes. The quality of the studies was appraised using the JBI Critical Appraisal Checklists for risk of bias, study design, and quality of evidence. Data syntheses were conducted following a simplified approach by Popay et al. Themes were developed based on the findings. Five randomized controlled trials met the inclusion criteria. The risk of bias was determined low in most of the studies. Text messages were the most common method. Pedometer, accelerometer, and International Physical Activity Questionnaires were commonly used to quantify the level of physical activity. Frequent reminders using text messages to the participants were the common strategy to ensure their adherence. The telehealth intervention has not yet shown significant positive effects on physical activity in people with diabetes mellitus. Further studies conducting synchronous and hybrid telehealth to improve physical activity in adults with diabetes mellitus were needed. Abstrak: Aktivitas fisik telah dievaluasi untuk menurunkan angka kematian pada penderita diabetes mellitus. Setelah pandemi COVID-19, pemberian layanan kesehatan condong ke telemedicine atau telehealth untuk melakukan social distancing. Tujuan utama dari tinjauan ini adalah untuk mengevaluasi format dan strategi yang digunakan dalam telemedicine untuk meningkatkan aktivitas fisik pada orang dewasa dengan diabetes mellitus. ProQuest, Medline, dan CINAHL dicari untuk penelitian yang melibatkan orang dewasa dengan diabetes mellitus (lebih dari 18 tahun); telemedis; dan hasil aktivitas fisik. Kualitas studi dinilai menggunakan JBI Critical Appraisal Checklists untukrisiko bias, desain studi, dan kualitas bukti. Sintesis data dilakukan mengikuti pendekatan yang disederhanakan oleh Popay et al. Tema dikembangkan berdasarkan temuan. Lima uji coba terkontrol secara acak memenuhi criteria inklusi. Risiko bias ditentukan rendah di sebagian besar penelitian. Pesan teks adalah metode yang paling umum. Pedometer, akselerometer, dan Kuesioner Aktivitas Fisik Internasional biasanya digunakan untuk mengukur tingkat aktivitas fisik. Pengingat yang sering menggunakan pesan teks kepada para peserta adalah strategi umum untuk memastikan kepatuhan mereka. Intervensi telehealth belum menunjukkan efek positif yang signifikan terhadap aktivitas fisik pada penderita diabetes mellitus. Diperlukan penelitian lebih lanjut yang melakukan telehealth sinkron dan hibrida untuk meningkatkan aktivitas fisik pada orang dewasa dengan diabetes mellitus.